文学认知研究的精妙科学 = Wen xue ren zhi yan jiu de jing miao ke xue - Stockwell, Peter (Sichuan International Studies University, 2012)
This paper reviews some key issues in the current study of cognitive poetics． It first explores the range of cognitive poetics，emphasizing the centrality of textuality and texture in cognitive poetics． Then it follows to outline different approaches to cognitive poetics and put forward some important principles of cognitive poetics． Lastly，it concludes the aesthetic and ethic tendency in cognitive literary studies，assuming that the connection of meaning，feeling and moral relationships allows cognitive poetics to encompass an integrated account of literature，which in turn aspires towards a reasonable account of consciousness in literary reading．